The Use of Gamification in Arabic Vocabulary Learning: A Literature Study - Aza, Fahema Hadia; Renata, Yessica Tiara; Faiqoh, Putri Kholida (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2025)
In the digital era, teachers are required to integrate technology optimally in learning. One of the methods used in learning Arabic vocabulary is gamification. The approach in this research uses a literature study. Literature study is conducted by collecting references consisting of several previous studies, then compiled to draw conclusions. To maintain the accuracy of the content, the researcher will re-read carefully the collected literature. The purpose of this study is to describe the use of gamification in learning Arabic vocabulary and identify digital platforms that support it. The results obtained from several game platforms, including Kahoot!, Wayground, Wordwall, and Educaplay, can be used as media for learning Arabic vocabulary. However, there are challenges in implementing gamification methods, such as limited tools and teacher skills in utilising the platform. Therefore, some actions are needed, such as digital integrated learning training and training in memorizing Arabic vocabulary, so that gamification-based learning can be applied optimally.